Medication Reconciliation Limitations: Observation of the Medication Reconciliation Process in the Emergency Department by Two Immersion Pharmacy Students - Christine Chong; Amanda Haile (University of Minnesota Libraries Publishing, 2016)
Multiple medical records may exist for a particular individual based on the various health services he or she receives. Maintaining updated, accurate records remains the responsibility of both practitioners and patients. Medication reconciliation, defined as the process to accurately depict the patient's current orders and medications, 2 seeks to avoid errors in duplicity, interactions and dosing errors. Medication histories at Moses Cone Hospital are currently recorded by pharmacy technicians who follow specific standards, for instance they cannot remove "house meds", which are prescribed medications with an active prescription attached. Technicians instead mark these medications for removal, leaving reconciliation to the physician. The physicians in the emergency department are not required to complete a full reconciliation for patient's profiles as this is a task left for the admitting physician. This leads to the question whether the reconciliation process in the emergency department (ED) needs to be re-evaluated. Patients' "After Visit Summary" reports were used to analyze patient profiles in determining medication reconciliation statuses (whether fully reconciled, partially reconciled, or unreconciled). 280 patients' profiles were used. 243 records (86.79%) were found unreconciled, 18 (6.43%) were partially reconciled, and 19 (6.79%) were fully reconciled. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties   Type: Student Project